Social security and gender inequality - Liudmila Malyshava; Brandon McCoy (Levy Economics Institute of Bard College, 2024)
This inquiry examines the role of federal policy in gender inequality using the principles of institutional adjustment (Foster 1981; Bush 1987) in the context of the Veblenian dichotomy of habit formation. Specifically, the authors assert that Social Security, though exclusive at its inception in 1935, has undergone significant institutional adjustment. Today, Social Security plays a determining role in providing the appropriate institutional space for not only increasing economic security for older women, but also for reducing gender inequality overall.
Keywords: B25; B5; I38; J1; N3; 330; gender disparities; Social Security; evolutionary policy analysis; economic security; retirement